Evaluation of lashing systems for onshore heavy module transportation: a quantitative analysis of securing force and sliding force - Mutadi (Journal of Emerging Innovations in Engineering, 2026)
The onshore transportation of heavy modules requires a reliable lashing securing system to prevent cargo shifting, which can lead to accidents and economic losses. This study evaluates the effectiveness of a lashing system used for transporting a heavy industrial component by land. A quantitative method was employed, comparing the total securing force provided by the lashing system against the sliding force induced by vehicle acceleration, braking, and cornering. Technical data on the lashing system, module specifications, and friction coefficients were obtained from field surveys and technical documents. The results show that the total securing force of the optimized lashing system is 2.49 MT, which exceeds the maximum sliding force of 1.87 MT under emergency braking conditions. The resulting safety ratio of 1.33 meets the minimum requirements of DNVGL-ST-N001 and the IMO CSS Code. A sensitivity analysis indicates that the lashing angle and contact surface friction coefficient are the most influential parameters. This study concludes that the evaluated lashing system is safe and applicable to similar transportation operations. Recommendations are provided regarding periodic inspections and optimization of lashing configurations.